The Legality of Diplomas as Debt Guarantee in Civil Law (Case Study of RY Pawning His Friend's Two Diplomas) - Maharani, Citra Ayu Deswina (Riviera Publishing, 2024)
A diploma is a graduation document of a student or student who has completed his or her study program. In this case, a diploma is a service because its value does not lie in its physical form, but in the meaning and function it has, namely proof that a person has successfully completed a certain educational program. However, in several guarantee institutions spread across Indonesia, there are still many who allow diplomas as an object of guarantee. In fact, the guarantee law is a closed law to protect the parties involved and is also a general guideline so that it cannot be arbitrarily modified. The closure of the guarantee law for the parties involved raises the question of whether the diploma as a guarantee means modifying the guarantee law that has been set by the state. Therefore, the author wants to examine the legality of a diploma as collateral for debt in civil law in order to find out whether the diploma already has a basis in civil law as a guarantee and how to process how to settle in case of default by the debtor who gives the diploma to be detained.